2019
DOI: 10.1111/jpc.14489
|View full text |Cite
|
Sign up to set email alerts
|

Weight status and diets of children aged 1–12 years attending a tertiary public paediatric outpatient clinic

Abstract: Aim: To assess the weight status and diets of a sample of paediatric outpatients, explore the relationship between the two and compare child weight status with parental perception of child weight and parents' self-reported weight. Methods: Parents/carers of 1-12-year-olds attending paediatric outpatients at Flinders Medical Centre, South Australia, between October 2015 and May 2016 completed a demographic and validated age-based dietary questionnaire (toddlers (1-3 years), pre-schoolers (>3 to <5 years) or chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Determining diet quality among child populations defined by weight status is crucial given the high prevalence of childhood obesity present in the United States. The relationship between diet quality and weight status in children has been studied by others, but results are inconclusive because both negative and positive associations have been reported . Several sociodemographic factors have been associated with diet quality in children, including socio‐economic status (positive association), age (negative association), sex (higher for girls), race/ethnicity (lower for black children, higher for Mexican American children), and geographic location (lower for rural) , but their interactions with weight status have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…Determining diet quality among child populations defined by weight status is crucial given the high prevalence of childhood obesity present in the United States. The relationship between diet quality and weight status in children has been studied by others, but results are inconclusive because both negative and positive associations have been reported . Several sociodemographic factors have been associated with diet quality in children, including socio‐economic status (positive association), age (negative association), sex (higher for girls), race/ethnicity (lower for black children, higher for Mexican American children), and geographic location (lower for rural) , but their interactions with weight status have not been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Perceived barriers to exercise and calcium intake were found to be low in this study, as seen in previous research. [29,30] This is contrary to a study done in Egypt that found high perceived barriers to both exercise and calcium intake attributed mainly to their spouse discouraging them from exercising. [28] We noted that less than half the patients could correlate caffeine use, smoking, and alcohol consumption to the risk of osteoporosis.…”
Section: Discussionmentioning
confidence: 88%
“…[28] The participants in this study had moderate perceived benefits to calcium intake and exercises, which is in keeping with a study done in Turkey and Peru. [27,29] However, Akinpetide in the US found higher scores, possibly due to the majority of the participants having a tertiary level of education. [30] Perceived barriers to exercise and calcium intake were found to be low in this study, as seen in previous research.…”
Section: Discussionmentioning
confidence: 99%